Resource Allocation in OFDMA as an Optimization Problem (2014)
Wireless mobile communication systems (WMCS) face the challenge of satisfying the requirements of an increasing number of users demanding diverse services. WMCS service providers have multiple challenges: increasing number of users, full satisfaction of service requirements, and introduction of new technologies. Adequate resource management becomes a key factor for guaranteeing a successful relationship between service provider and users, for meeting system performance goals, and to achieve financial sustainability.